2014
DOI: 10.5125/jkaoms.2014.40.3.103
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of soft tissue asymmetry using cone-beam computed tomography after open reduction and internal fixation of zygomaticomaxillary complex fracture

Abstract: ObjectivesIn this study, we assessed soft tissue asymmetry that occurred after open reduction of unilateral zygomaticomaxillary complex (ZMC) fractures. We proposed a simple method to assess soft tissue asymmetry after reduction surgery by evaluating the symmetry between the affected and the unaffected sides. The factors affecting soft tissue contour after surgery were also analyzed.Materials and MethodsSubjects included patients admitted to Wonkwang University Dental Hospital from 2008 to 2013. Cone-beam comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…explanation of this, type of fracture was unilateral ZMC feature in our study .This matched with Khaqani et al (15) who reported that the type of ZMC fracture greatly influences the outcome of ZMC fracture treatment. In the same side with the present results, and Kim et al (27) also reported a higher degree of asymmetry for comminuted ZMC fractures Madkour (28) reported that MDCT is the principle diagnostic imaging tool in maxillofacial trauma. Multiplanar reformatted (MPR) and three-dimensional (3D)-reconstructed images provide a detailed analysis for midfacial fractures and assessment of their severity.…”
Section: Discussionsupporting
confidence: 90%
“…explanation of this, type of fracture was unilateral ZMC feature in our study .This matched with Khaqani et al (15) who reported that the type of ZMC fracture greatly influences the outcome of ZMC fracture treatment. In the same side with the present results, and Kim et al (27) also reported a higher degree of asymmetry for comminuted ZMC fractures Madkour (28) reported that MDCT is the principle diagnostic imaging tool in maxillofacial trauma. Multiplanar reformatted (MPR) and three-dimensional (3D)-reconstructed images provide a detailed analysis for midfacial fractures and assessment of their severity.…”
Section: Discussionsupporting
confidence: 90%
“…In the detailed description of malar asymmetry including soft tissue reported by Kim et al [ 12 ], a statistically significant malar depression was observed even after surgery in anteroposterior dimension. Kim et al [ 12 ] reported no significant difference in bilateral position of hard tissue landmarks after open reduction and internal fixation in patients with ZMC fracture, but soft tissue depression was confirmed after surgery. Soft tissue depression around zygoma would be more noticeable if reduction were not accurate and was more noticeable when titanium was used in comparison to biodegradable plates [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [ 12 ] reported no significant difference in bilateral position of hard tissue landmarks after open reduction and internal fixation in patients with ZMC fracture, but soft tissue depression was confirmed after surgery. Soft tissue depression around zygoma would be more noticeable if reduction were not accurate and was more noticeable when titanium was used in comparison to biodegradable plates [ 12 ]. Considering the results of our study and the occurrence of soft tissue depression after surgery, we carefully suggest an overcorrection surgical technique and follow-up studies about the methods of overcorrection technique are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the zygomaticomaxillary complex fracture type significantly impacts its treatment outcome. Kim et al [30]. also showed that comminuted zygomaticomaxillary complex fractures have a higher level of asymmetry.…”
Section: Reports For the Zygomatic Complex Fracturesmentioning
confidence: 95%